Inflation and its effect on marketing - Consumer buying behavior in Latakia governorate. - صقر إبراهيم حمدان; علي غيث أمين (Latakia University Journal -Biological Sciences Series, 2020)
Using descriptive analysis to study the effect of rising prices on consumer buying behavior in Latakia governorate, we selected a sample of 70 consumers. After analyzing the data, the study showed that there is an influence of the consumer’s income level on buying behavior for clothes shopping from the secondhand clothing markets. as well as for foods shopping from the Pallets and sidewalks, and there is an influence of the consumer’s education level and address on buying behavior for foods shopping from the Pallets and sidewalks, as well as for foods shopping of unknown source and data. Research results showed that 84.3% sample members are shopping these clothes or some of it from the secondhand clothing markets, and 54.2% from these this behavior had happened after the crisis. and 57.1% of the study sample reduced the clothes purchase as a solution to the problem of rising prices, while 42.9% preferred to continue buying clothes, this was at the expense of quality. As for the foods, study also showed that 58.6% of sample members have no objections to shopping food from the Pallets and sidewalks, and about half of this behavior was before the crisis, because of low level of income. In order to solve the problem of rising prices, 72.9% of the study sample resorted to limiting the buy of expensive foods, while 27.1% resorted to buying lower quality food, because its price is lower. About 65.7% of the sample members were most concerned about the price at the expense of quality when buying clothes, as there is a clear effect of inflation on their buying behavior, while this effect was somewhat reduced when buying food.